DESIGN OF ELECTRONIC CONTROL GOVERNOR FOR A SINGLE CYLINDER GASOLINE ENGINE BASED ON AN INTELLIGENT SENSING ALGORITHM - Sun,Lixiang (2020)
ABSTRACT At present, most large machinery and vehicle engines are electronically controlled but their electronic control systems are too expensive to be popularised and applied in small gasoline engines with relatively low prices. Therefore, small gasoline engines still use mechanical speed regulators. Mechanical speed regulators not only have the defects of inertia lag, friction resistance, inherent speed regulation and the like, but also have the disadvantage that dynamic performance and steady performance cannot be combined, which is not suitable for the increasingly improved speed regulation performance of gasoline engines. This paper describes the design of an electronically controlled intelligent governor for small gasoline engines. Starting from a low cost, it adopts the idea of “replacing part of the hardware with an intelligent sensing algorithm” and proposes an intelligent sensing algorithm scheme. It combines the “coarse tuning” of MAP and the “fine tuning” of adaptive expert PID. The system is proved experimentally and it not only overcomes the inherent defects of a mechanical governor and realises programmable speed regulation, but it also obtains good dynamic and steady performance, improves the power output of the engine, relieves the trouble of engine travelling and improves the freedom of carburetor matching.